Honor de Cavalleria, riflessioni sul ‘Quijjote’ di Albert Serra - Palladino, Nicola (Rassegna Iberistica, 2018)
This article discusses the cinematographic adaptation of Cervantes’ Don Quijote done by Spanish director Albert Serra (2006). Honor de cavalleria, which became a book in 2010, confounded and baffled Spanish critics for its lack of ‘adventures’, dialogues and characters, and the unaffected performances of the cast: El Quijote (Lluís Carbó) and Sancho (Lluís Serrat) lost in a row landscapes. The article considers the validity and strength of Serra’s controversial setting, taking into consideration some Quijote’s cinematographic ‘models’ and adaptations.